2010
DOI: 10.1073/pnas.1007518107
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific assembly of FtsK hexamers establishes directional translocation on DNA

Abstract: FtsK is a homohexameric, RecA-like dsDNA translocase that plays a key role in bacterial chromosome segregation. The FtsK regulatory γ-subdomain determines directionality of translocation through its interaction with specific 8 base pair chromosomal sequences [(KOPS); FtsK Orienting / Polarizing Sequence(s)] that are cooriented with the direction of replication in the chromosome. We use millisecond-resolution ensemble translocation and ATPase assays to analyze the assembly, initiation, and translocation of FtsK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 23 publications
6
60
10
Order By: Relevance
“…Our data suggest that FtsK is preferentially loaded at KOPS only under conditions in which ATP hydrolysis is prevented. This finding contrasts with bulk biochemical assays, which have suggested that FtsK loads at KOPS when ATP is used as the nucleotide cofactor (9). One explanation for this discrepancy is that prior bulk assays used relatively short DNA substrates with a correspondingly high density of KOPS sites, ranging from 1 KOPS per 30 bp up to 1 KOPS per 336 bp.…”
Section: Model For Kops-specific Loading Of Ftsk In the Absence Of Atpcontrasting
confidence: 52%
See 3 more Smart Citations
“…Our data suggest that FtsK is preferentially loaded at KOPS only under conditions in which ATP hydrolysis is prevented. This finding contrasts with bulk biochemical assays, which have suggested that FtsK loads at KOPS when ATP is used as the nucleotide cofactor (9). One explanation for this discrepancy is that prior bulk assays used relatively short DNA substrates with a correspondingly high density of KOPS sites, ranging from 1 KOPS per 30 bp up to 1 KOPS per 336 bp.…”
Section: Model For Kops-specific Loading Of Ftsk In the Absence Of Atpcontrasting
confidence: 52%
“…Given the abundance of ATP in vivo, and the finding that KOPS recognition is suppressed even in ADP/ATP mixtures, we speculate that cooperative stepwise assembly of FtsK hexamers from monomeric subunits at KOPS may be used as a mechanism for regulating the initiation of translocation, as previously suggested (5,6,9,23). Such a model would presume that complete hexamer assembly from monomers is inefficient on nonspecific DNA and that ATP hydrolysis is inhibited until the hexamer is fully assembled at KOPS.…”
Section: Model For Kops-specific Loading Of Ftsk In the Absence Of Atpmentioning
confidence: 82%
See 2 more Smart Citations
“…However, translocation appears to be a prerequisite for activation in the natural situation (i.e., when FtsKγ is linked to the FtsK motor). This can be inferred from the incapacity of FtsK mutants defective in translocation (i.e., unable to hydrolyze ATP) to induce recombination (29,30). We further show that an active FtsK motor also fails to activate recombination if unable to stop at the recombination complex.…”
Section: Discussionmentioning
confidence: 90%